Evaluación del programa de articulación a partir de historias de vida de estudiantes de una IED de la localidad de Bosa - Barrera Duitama, Sandra Juliana
Within the articulation program in the CGA there has been some research that aims to evaluate the impact of this program on students who received this technical education. This article arises in this context and it is going to present the life stories of technical students who attend a public institution in Bosa related to the experience of education they have been receiving from their school and from SENA. This text takes the advantages of qualitative approach, it systematizes the information collected by the life stories technique. For achieving the aim, the article is goingto be divided into: introduction, methodology and the authors quoted; a description of the most important findings and its categories; and finally, the conclusion that allow to recognize the role played by technical training in this particular context.